Differentially Regulated Orthologs in Sorghum and the Subgenomes of Maize. Issue 8 (21st July 2017) - Zhang, Yang; Ngu, Daniel W.; Carvalho, Daniel; Liang, Zhikai; Qiu, Yumou; Roston, Rebecca L.; Schnable, James C.
Abstract : The response of the same genes to cold stress often varies between maize and sorghum, but the set of genes with conserved patterns of regulation show greater evidence of functional constraint. Abstract: Identifying interspecies changes in gene regulation, one of the two primary sources of phenotypic variation, is challenging on a genome-wide scale. The use of paired time-course data on cold-responsive gene expression in maize ( Zea mays ) and sorghum ( Sorghum bicolor ) allowed us to identify differentially regulated orthologs. While the majority of cold-responsive transcriptional regulation of conserved gene pairs is species specific, the initial transcriptional responses to cold appear to be more conserved than later responses. In maize, the promoters of genes with conserved transcriptional responses to cold tend to contain more micrococcal nuclease hypersensitive sites in their promoters, a proxy for open chromatin. Genes with conserved patterns of transcriptional regulation between the two species show lower ratios of nonsynonymous to synonymous substitutions. Genes involved in lipid metabolism, known to be involved in cold acclimation, tended to show consistent regulation in both species. Genes with species-specific cold responses did not cluster in particular pathways nor were they enriched in particular functional categories. We propose that cold-responsive transcriptional regulation in individual species may not be a reliable marker for function, while a core set of genes involved in perceiving and responding to cold stress are subject to functionally constrained cold-responsive regulation across the grass tribe Andropogoneae.